2017
DOI: 10.1186/s12967-017-1197-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling and quantitative high-throughput (qHTS) drug screening of CDH1 deficient hereditary diffuse gastric cancer (HDGC) cells identify treatment leads for familial gastric cancer

Abstract: BackgroundPatients with hereditary diffuse gastric cancer (HDGC), a cancer predisposition syndrome associated with germline mutations of the CDH1 (E-cadherin) gene, have few effective treatment options. Despite marked differences in natural history, histopathology, and genetic profile to patients afflicted by sporadic gastric cancer, patients with HDGC receive, in large, identical systemic regimens. The lack of a robust preclinical in vitro system suitable for effective drug screening has been one of the obsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
(63 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, Ping et al ( 37 ) reported that decreased CXCL12 in the tumor microenvironment may facilitate lymphoid malignant cells metastasis by limiting the interactions between malignant cells and surrounding cells in lymphocytic leukemia. CDH1 , as a member of the cadherin superfamily, may serve a critical role in apoptotic process and cell-cell adhesion ( 38 ). A previous study demonstrated that CDH1 expression was lower in gastric cancer and this decrease contributed to intestinal-type gastric carcinogenesis ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ping et al ( 37 ) reported that decreased CXCL12 in the tumor microenvironment may facilitate lymphoid malignant cells metastasis by limiting the interactions between malignant cells and surrounding cells in lymphocytic leukemia. CDH1 , as a member of the cadherin superfamily, may serve a critical role in apoptotic process and cell-cell adhesion ( 38 ). A previous study demonstrated that CDH1 expression was lower in gastric cancer and this decrease contributed to intestinal-type gastric carcinogenesis ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…c.1380delA CDH1mutant cells were selectively sensitive to inhibition of the EGFR effectors PI3K, mTOR, MEK, c-Src, FAK, and TOPO2 inhibition. The drug phenotype overlapped with the top two signaling networks found enriched by Meta-Core analysis in c.1380delA cells [12]. The highest-ranking network predicted to be enriched in c.1380delA cells included a number of signaling regulators of the enriched epidermal growth factor receptor signaling pathway or inositol triphosphate (IP3)/diacylglyercol (DAG) signaling which directly or indirectly overlapped with the drug phenotype of enhanced sensitivity against MEK, mTOR, FAK, or PKC activity anti-PKC, c-Src kinase, and FAK activity.…”
Section: High-throughput Drug Screening In Cell-based Models Of Hdgcmentioning
confidence: 95%
“…As no effective systemic therapies are available for HDGC, an initial broad evaluation of potential drug targets is desirable. Our group conducted a differential high-throughput drug screen in gastric cancer cells derived from a stage IV HDGC patient with a truncating c.1380delA CDH1 germline mutation and gastric cancer cells derived from a liver lesion of a gastric cancer patient with wild type CDH1 [12]. The drug library utilized for screening was enriched for oncology compounds and contained multiple compounds per class to detect class effects.…”
Section: High-throughput Drug Screening In Cell-based Models Of Hdgcmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of gastric carcinoma (GC) varies between males and females [1,2], among individual nations and regions of the world [3,4], and is associated with infectious [5][6][7], environmental [8,9], and genetic [10,11] factors.…”
Section: Introductionmentioning
confidence: 99%